ACG Clinical Guideline: Gastroparesis - Camilleri, Michael; Kuo, Braden; Nguyen, Linda; Vaughn, Vida M.; Petrey, Jessica; Greer, Katarina; Yadlapati, Rena; Abell, Thomas L. (The American journal of gastroenterology, 2022)
Gastroparesis is characterized by symptoms suggesting retention of food in the stomach with objective evidence of delayed gastric emptying in the absence of mechanical obstruction in the gastric outflow. This condition is increasingly encountered in clinical practice. These guidelines summarize perspectives on the risk factors, diagnosis, and management of gastroparesis in adults (including dietary, pharmacological, device, and interventions directed at the pylorus), and they represent the official practice recommendations of the American College of Gastroenterology. The scientific evidence for these guidelines was assessed using the Grading of Recommendations, Assessment, Development, and Evaluation process. When the evidence was not appropriate for Grading of Recommendations, Assessment, Development, and Evaluation, we used expert consensus to develop key concept statements. These guidelines should be considered as preferred but are not the only approaches to these conditions.